Kinetics of Isothermal Annealing of Chlorite in γ-Irradiated Lanthanum chlorate Hexahydrate and Lanthanum Chlorate Monohydrate Crystals - Lokhande, R.S.; Kelkar, S.S. (Asian Journal of Chemistry, 2010)
Kinetics of thermal annealing of chlorite in the γ-radiolysis of lanthanum chlorate hexahydrate crystals and lanthanum chlorate monohydrate crystals has been studied at different temperatures in the range of 85–155ºC. The chlorite is found to anneal by the combination of first and second order processes. The former being fast virtually reaches completion within a few hours. This process is then followed by a second order process which is observed to be a slow process. The annealing pattern of chlorite in both the systems is observed to be same. A suitable mechanism of annealing process is proposed.